2022
DOI: 10.1111/1365-2745.13844
|View full text |Cite
|
Sign up to set email alerts
|

Making (remote) sense of lianas

Abstract: Lianas (woody vines) are abundant and diverse, particularly in tropical ecosystems. Lianas use trees for structural support to reach the forest canopy, often putting leaves above their host tree. Thus they are major parts of many forest canopies. Yet, relatively little is known about distributions of lianas in tropical forest canopies, because studying those canopies is challenging. This knowledge gap is urgent to address because lianas compete strongly with trees, reduce forest carbon uptake and are thought t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 144 publications
(235 reference statements)
1
7
0
Order By: Relevance
“…Our results indicated that green and shortwave infrared wavelength regions were especially important for detecting the ferns and vines within the dense vegetation of tropical rainforests (Figure 5). This result is consistent with the previous reports that showed the potential of the visible green wavelength or shortwave infrared region to separate liana or fern from trees [21,[23][24][25][26]28,77]. On the other hand, the individual near-infrared wavelength region was less important, but vegetation indices calculated based on near-infrared regions with green (NDWI) or SWIR2 (NBR) were effective.…”
Section: The Important Variables For Detecting the Fern-vine Continuu...supporting
confidence: 92%
See 1 more Smart Citation
“…Our results indicated that green and shortwave infrared wavelength regions were especially important for detecting the ferns and vines within the dense vegetation of tropical rainforests (Figure 5). This result is consistent with the previous reports that showed the potential of the visible green wavelength or shortwave infrared region to separate liana or fern from trees [21,[23][24][25][26]28,77]. On the other hand, the individual near-infrared wavelength region was less important, but vegetation indices calculated based on near-infrared regions with green (NDWI) or SWIR2 (NBR) were effective.…”
Section: The Important Variables For Detecting the Fern-vine Continuu...supporting
confidence: 92%
“…The wavelength regions that are important for distinguishing ferns or vines from trees have been reported variously. For canopy-level separation between vines and trees in tropical forests, detailed studies using hyperspectral spectroscopy have been conducted and two wavelength regions have been reported to be important [24]: the visible green region, which represents the characteristics of chlorophyll and carotenoid concentration [21,[25][26][27], and the shortwave infrared (SWIR) region, which represents water content [26,27]. When using a multispectral optical satellite sensor, the visible green region of Sentinel-2 is especially helpful [23].…”
Section: Introductionmentioning
confidence: 99%
“…A review of the recent progress made in the study of liana ecology using terrestrial, aerial, and space‐based remote sensing is provided by Heijden et al. (2022).…”
Section: Discussionmentioning
confidence: 99%
“…Our approach does not take into account the species in the lower layers of the canopy. A review of the recent progress made in the study of liana ecology using terrestrial, aerial, and space-based remote sensing is provided by Heijden et al (2022).…”
Section: Partial Estimation Of Biodiversity Of Tropical Forestmentioning
confidence: 99%
“…We lack information on the influence and interaction of the multiple hypothesised influences on liana distributions at the landscape scale, particularly in tropical forest tree crowns. This is partly due to reliance on ground‐based data collection, including liana stem measurements, as opposed to canopy occupancy, which can be difficult to assess from the ground (Marvin et al, 2016; van der Heijden et al, 2022; Waite et al, 2019). Liana canopy occupancy may be more directly related to liana–tree competition, however, as lianas deploy most of their leaves above those of their host trees (Avalos & Mulkey, 1999; Rodríguez‐Ronderos et al, 2016), directly reducing the amount of light received and the photosynthetic capacity of their host trees (Avalos et al, 1999; Avalos & Mulkey, 1999; Fauset et al, 2017).…”
Section: Introductionmentioning
confidence: 99%